Book review: Albert E. Trieschman, James K. Whittaker and Larry K. Brendtro Piscataway, (1962). The Other 23 Hours. New Jersey, Aldine Transaction, 240pp. ISBN 0202260860 - Kirsty Hamilton (Scottish Journal of Residential Child Care)
K. Brendtro, attempts to provide a framework for understanding and using the milieu as a therapeutic tool that helps to support, nourish and assist with vulnerable and traumatised children's development. Within the book the milieu is described as the surroundings or environment in which the children and young people live. The authors work from the premise that 'the action of adults with children and the adults' control of the environment can be co-ordinated to improve children's lives' (p.1). The majority of the observations came from the Walker Home for Children in Massachusetts. The authors described this home as a residential centre for 'severely disturbed, acting-out boys' (p.xii).